Acceptance of recommended vaccinations during pregnancy: a cross-sectional study in Southern Italy - Licata, Francesca; Romeo, Marika; Riillo, Concetta; Di Gennaro, Gianfranco; Bianco, Aida (Frontiers in Public Health, 2023)
Background: Vaccine administration is a recommended, safe and effective to protect them against vaccine-preventable diseases (VPDs). Despite available guidance, maternal immunization rates counter against influenza and Tetanus Toxoid, Reduced Diphtheria Toxoid, and Reduced Acellular Pertussis (Tdap) in Italy remain incredibly low. The primary goal of the study was to explore what Italian pregnant women knew about VPDs and immunisation during pregnancy, and what factors affected their decision to be vaccinated. Methods: This cross-sectional study took place between October 2021 and April 2022 in Southern part of Italy. All consecutive pregnant women, from those attending the selected facilities in randomly selected days, were approached to request participation. The inclusion criteria for participation were age ≥ 18 years, ability to understand, speak and read Italian and being pregnant at any gestational age. The questionnaire, using a combination of checkboxes and free text answers, consisted of 32 items divided into 5 parts and lasted about ten minutes. Results: The results showed that 61% understood that the influenza vaccine is recommended, and 48.7% knew that influenza could be risky during pregnancy; 74.1% wrongly reported that the Measles-Mumps-Rubella vaccine is recommended during pregnancy. Seven out of ten pregnant women believed that strong evidence support safety of vaccinations during pregnancy and more than half (55.6%) thought to be at increased risk of severe illness with COVID-19. Women in the sample believed that vaccines received during pregnancy pose risk of adverse events to unborn child with a median value of 6 (IQR 3-9), on a scale ranging from 1 to 10. Similarly, the fear of contracting pertussis and influenza during pregnancy showed a median value of 6 (IQR. 3-9) and 5 (IQR. 3-8), respectively. Only 21.1% and 36.5% of women recived influenza and Tdap vaccine during pregnancy. Conclusions: The crucial factors in the process of encouraging pregnant women to get vaccinated are improving the understanding of women's experiences and perceptions about vaccines and training women to critically evaluate information to reach a good level of vaccine coverage. More effective communication strategies have to take into account drivers of vaccine hesitancy in the local context.